2008
DOI: 10.1007/s10562-008-9779-8
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Dimethyl Ether over Modified H-Mordenite Zeolites and Bifunctional Catalysts Composed of Cu/ZnO/ZrO2 and Modified H-Mordenite Zeolite in Slurry Phase

Abstract: Synthesis of dimethyl ether (DME) via methanol dehydration were investigated over various catalysts, and via direct CO hydrogenation over hybrid catalysts composed of Al-modified H-Mordenite zeolite and Cu/ZnO/ZrO 2 . H-Mordenite zeolite exhibited the highest activity in dehydration of methanol. However, its selectivity toward dimethyl ether was rather low. For this reason, the H-Mordenite was modified. Modification of zeolites was performed by wet impregnation method and considered catalysts were characterize… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0
4

Year Published

2010
2010
2016
2016

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 36 publications
0
12
0
4
Order By: Relevance
“…Indeed, in most of the previous works, ZSM-5 (MFI, 10-ring pore system) has been the zeolite of choice as the methanol dehydration component of the bifunctional catalysts [8,9,13,16,24,25,26,27,28,29,30,31,32,33]. Besides MFI, other 10-ring pore structures such as FER (ferrierite) [10,14,34] and MWW (MCM-22, MCM-49) [15,35,36] as well as 12-ring pore systems such as FAU (Y) [13,14,37,38,39,40] and MOR (mordenite) [37,41] have also been studied. Unfortunately, any attempt to gather general conclusions regarding topological effects from the aforementioned studies have been discouraging given the disparity in catalyst composition, preparation method, and reaction conditions.…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, in most of the previous works, ZSM-5 (MFI, 10-ring pore system) has been the zeolite of choice as the methanol dehydration component of the bifunctional catalysts [8,9,13,16,24,25,26,27,28,29,30,31,32,33]. Besides MFI, other 10-ring pore structures such as FER (ferrierite) [10,14,34] and MWW (MCM-22, MCM-49) [15,35,36] as well as 12-ring pore systems such as FAU (Y) [13,14,37,38,39,40] and MOR (mordenite) [37,41] have also been studied. Unfortunately, any attempt to gather general conclusions regarding topological effects from the aforementioned studies have been discouraging given the disparity in catalyst composition, preparation method, and reaction conditions.…”
Section: Introductionmentioning
confidence: 99%
“…In our previous study, we showed that the appropriate molar ratio of elements in the bifunctional catalyst (hydrogenation to dehydration) was 2:1 (Khandan et al 2009). Therefore, bifunctional catalysts (Cu/ZnO/ZrO 2 : 46/46/8 on Al-modified H-mordenite zeolite) were prepared with a molar ratio of 2:1 and using the co-precipitation sedimentation method (Ge et al 1998).…”
Section: Catalyst Preparationmentioning
confidence: 99%
“…Among different zeolites, HZSM-5 has been, so far, the most widely investigated for the STD process [127,128,130], though good catalytic results have also been reported for other zeolites such as HY [127], H-mordenite (HMOR) [131], HMCM-22 [132], and H-ferrierite (HFER) [133], as well as for microporous SAPOs [134].…”
Section: One-step Synthesis Of Dimethyl Ether (Dme) From Syngasmentioning
confidence: 99%
“…Very interestingly, on the basis of their results, these authors proposed a mechanism for the dehydration of methanol on the MgO-modified HZSM-5 zeolite that involves, as the initial steps, a strong adsorption of MeOH on an acidic site and a weak adsorption of alcohol on a neighboring basic site [142]. Modification of the zeolite with other basic oxides, such as CaO [143], and by impregnation with solutions containing certain transition metals (e.g., Zr, Ni, Al) [131,144,145] leads to redistribution of the zeolite acid strength toward weaker sites with the consequent improvement in DME selectivity and on-stream stability. Other strategies that have been applied to reduce the strong acidity in the dehydration zeolite component and thus to improve DME selectivity (by suppressing secondary reactions) involve dealumination of the parent zeolite by steaming and acid treatments [132].…”
Section: One-step Synthesis Of Dimethyl Ether (Dme) From Syngasmentioning
confidence: 99%